1988
DOI: 10.1177/089270578800100104
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Thermogravimetric Properties of Polyphenylene Sulfide and Polyetherether Ketone Resins and Composites

Abstract: Polyphenylene sulfide (PPS) and Polyetherether ketone are high performance engineering thermoplastics with a unique combination of excellent thermal, mechanical and environmental properties. This paper presents the thermogravimetric properties of PPS and PEEK resins and carbon fiber reinforced composites. The addition of carbon fiber and the effects of environment on the thermal stability are presented. Crosslinking of Polyphenylene sulfide in air enhances thermal stability is discussed. PEEK resin and its com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 4 publications
(4 reference statements)
1
6
0
Order By: Relevance
“…For anisothermal conditions, it was noticed that the temperature of the decomposition onset (Td,onset) shifts to higher temperature with increasing the heating rate, whether the testing atmosphere is oxidizing or not. Regarding C/PPS composites, it was reported that the presence of carbon fibres delays the onset of pyrolysis under oxidizing atmosphere, in agreement with conclusions presented in the literature on PPS and PPS-based composites [12]. The activation energy calculated from MT-TGA suggests the existence of three different mechanisms during pyrolysis under inert atmosphere: depolymerization, random chain scission and ultimately cyclisation (char formation) [7,10].…”
Section: Revised Manuscript With No Changes Markedsupporting
confidence: 86%
“…For anisothermal conditions, it was noticed that the temperature of the decomposition onset (Td,onset) shifts to higher temperature with increasing the heating rate, whether the testing atmosphere is oxidizing or not. Regarding C/PPS composites, it was reported that the presence of carbon fibres delays the onset of pyrolysis under oxidizing atmosphere, in agreement with conclusions presented in the literature on PPS and PPS-based composites [12]. The activation energy calculated from MT-TGA suggests the existence of three different mechanisms during pyrolysis under inert atmosphere: depolymerization, random chain scission and ultimately cyclisation (char formation) [7,10].…”
Section: Revised Manuscript With No Changes Markedsupporting
confidence: 86%
“…1 Among advanced thermoplastic polymers, polyphenylene sulfide (PPS) has been used widely in structural parts due to its easy processability, excellent tensile strength, flexural modulus, low water absorption, and appropriate thermal resistance. [1][2][3][4] However, in these structural applications, PPS is most commonly reinforced with carbon fibers (CF) fabrics. PPS/CF composites have also demonstrated good retention of mechanical properties and fiber-matrix adhesion under hot-wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The cross-linking mechanisms under air highlighted by Ma et al could partly explain this phenomenon. 33 At lower temperatures, as the decomposition of the decomposition is slow, partial cross-linking of the matrix in parallel could result in less extensive could result in less extensive pyrolysis and therefore earlier oxidation.…”
Section: Tga Resultsmentioning
confidence: 99%